2019
DOI: 10.4149/neo_2018_181130n910
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy comparison of targeted next-generation sequencing in the identification of somatic mutations in circulating tumor DNA from different stages of lung cancer

Abstract: This study aims to assess the potential clinical application of targeted next generation sequencing (NGS)-based deep sequencing for the detection of clinically relevant mutations in circulating tumor DNA (ctDNA) obtained from non-small cell lung cancer (NSCLC) patients. Targeted deep sequencing was performed to identify High Confidence Somatic Variants (HCSVs) in matched tumor tissue DNA (tDNA) and ctDNA in 50 NSCLC patients. Our results demonstrated that NSCLC patients with Stage IV (61.5%) exhibited a higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…A total of 20 publications corresponding to 20 studies were selected for inclusion (Figure 1). Sixteen studies [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] reported CV only, one study 60 reported CU only, and one study 61 provided information on both CV and CU.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 20 publications corresponding to 20 studies were selected for inclusion (Figure 1). Sixteen studies [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] reported CV only, one study 60 reported CU only, and one study 61 provided information on both CV and CU.…”
Section: Study Selectionmentioning
confidence: 99%
“…The majority of the included CV studies [45][46][47][49][50][51][53][54][55][56][57][58][59]61,62 used a prospective cohort design (83.3%, 15/18), and three studies 44,48,52 used retrospective medical record data. All studies evaluated ctDNA-based NGS technologies, with eleven studies [44][45][46][48][49][50][51][52]58,61,62 evaluating branded ctDNA tests and seven studies 47,[53][54][55][56][57]59 describing the ctDNA technologies without a specific brand name (Table 1).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Importantly, clinical evidence indicates that there is a substantial discordance in the genomic alterations and efficacy between the tumor tissue and blood ctDNA samples from the same patient. 8,9 Thus, it is important to carefully evaluate these different profiling methods in order to provide more information about whether ctDNA is useful for molecular diagnostics.…”
Section: Introductionmentioning
confidence: 99%